Action research in a teacher education program: probing into pre-service elementary teachers' understandings of scientific practices and teaching scientific practices - Saribas, Deniz; Ozer, Ferah (Journal of education for teaching : JET, 2022)
The study presented here is an action research that was conducted in a science and technology teaching course in a pre-service elementary teaching program at a private university in Turkey aiming at improving the pre-service elementary teachers' understanding of science and teaching science. In order to achieve this aim, an innovative approach, using Benzene Ring Heuristic (BRH) to introduce scientific practices (SPs) to pre-service elementary teachers was implemented in the study. This heuristic was used to illustrate the interrelatedness of cognitive-epistemic and social-institutional aspects of SPs in a holistic presentation. The data were gathered from various sources, including pre-service teachers' posters, individual lesson plans, and individual interviews. The results suggest that the method helped the pre-service teachers have a coherent and organised understanding of SPs; however, despite the increase in the usage of discourse and social certification, they still have difficulties understanding these issues. In light of evidence gathered from this study, further research includes deliberate attempts to encourage the pre-service teachers to integrate discourse and social certification in their own instruction.